Viewpoint: Integrated urban modeling: Past, present, and future - Miller, Eric J. (Journal of Transport and Land Use, 2018)
Integrated urban models (IUMs) (aka, integrated transport/land-use models) have been developed and (sometimes) applied for more than 50 years, dating back to the early 1960s. IUMs have been criticized over this same period on both practical and theoretical grounds. At the same time, continuing and very significant technological developments have made possible the development, implementation and use of such models in operational planning settings in various countries worldwide. A major review of the IUM state of the art and recommendations for evolution of this state were prepared by the author and colleagues 20 years ago. This paper presents an update of the 1998 report in terms of a summary of progress over the past 20 years, a critical assessment of the current IUM state of the art and practice, and needs and prospects for future development. This paper argues that the current modeling state is in “the doldrums,” similar to concerns raised by Pas in the seminal 1990 critique of activity-based travel models. It then outlines research and development needs to exploit current and emerging data, computing, and methodological developments that hold promise for the development of a much more powerful and useful “next generation” of IUMs.